Cucina - Shayma Abu Zahra; Rabab Saleh (My University, 2016)
An iOS social networking application, targeting people who like cooking and learning new recipes.User can share his own recipes with friends (can also share it on Facebook , twitter, Google plus). On the other hand, friends can comment, rate this recipe depending on the taste, cost and the way of serving, and can add it to their favourite meals.The user can search for recipes depending on its type ( dessert, drinks, etc) , its ingredients ( for example if want to bake a chocolate cake , then search for dessert recipe that contain chocolate), and its origin ( indian , italic recipes).For people who love to cooke,  this app will satisfy their interests, and may be this app can help them to find their dream job in a big restaurant.This application will be written in both swift and objective-c , will be compatible with iPhone, requires iOS 7 or later, in both languages English and Arabic.The API will be written in java using Eclipse, for the Database use WAMPP server.

. . : . . . . .
Cucina